2004
DOI: 10.1073/pnas.0304594101
|View full text |Cite
|
Sign up to set email alerts
|

The ecological and evolutionary consequences of sperm chemoattraction

Abstract: Chemical communication between sperm and egg is a critical factor mediating sexual reproduction. Sperm attractants may be significant evolutionarily for maintaining species barriers, and important ecologically for increasing gamete encounters. Still unresolved, however, are the functional consequences of these dissolved signal molecules. Here, we provide experimental evidence that sperm chemoattraction directly affects the magnitude of fertilization success. The recent discovery of L-tryptophan as a potent att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 29 publications
3
112
0
Order By: Relevance
“…However, these systems do vary in fundamentally different ways, which are likely to have important implications for fertilization success. First, pheromones and other chemotactic attractants may be used by some marine animals to increase fertilization success and outcrossing (for example, Coll et al, 1995;Riffell et al, 2002Riffell et al, , 2004, while filter feeding species have been shown to actively filter out and store sperm from conspecific individuals (Yund, 2000;Hughes et al, 2002). Nevertheless, levels of selfing may be more common in marine animals than is currently recognized and more research is clearly needed to determine the extent of selffertilization and the factors important in maintaining mixed reproductive strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these systems do vary in fundamentally different ways, which are likely to have important implications for fertilization success. First, pheromones and other chemotactic attractants may be used by some marine animals to increase fertilization success and outcrossing (for example, Coll et al, 1995;Riffell et al, 2002Riffell et al, , 2004, while filter feeding species have been shown to actively filter out and store sperm from conspecific individuals (Yund, 2000;Hughes et al, 2002). Nevertheless, levels of selfing may be more common in marine animals than is currently recognized and more research is clearly needed to determine the extent of selffertilization and the factors important in maintaining mixed reproductive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…While some plants have evolved associations with pollinators to assist in the transfer of pollen from one individual to another, no such associations are known for marine taxa. Although pheromones and other chemotactic attractants may be used by some marine taxa to increase fertilization success (for example, Coll et al, 1995;Riffell et al, 2002Riffell et al, , 2004, and despite the potential for decreased fitness due to inbreeding through selfing, the capacity to ensure fertilization in the absence of potential mates or under sperm-limited conditions means that self-fertilization may be an important reproductive tactic for hermaphroditic brooding and broadcast spawning species (for example, Sabbadin, 1971;Heyward and Babcock, 1986;Yund and McCartney, 1994;Cohen, 1996, Brazeau et al, 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm chemokinesis, on the other hand, describes a change in the steady-state speed of sperm cells, independent of direction, which is governed by the concentration of the chemical stimulus [16]. Both processes (hereafter 'sperm chemoattraction') can simultaneously contribute to the accumulation of sperm around unfertilized eggs [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Many marine invertebrate eggs have accessory structures, such as follicle cells or jelly coats, that increase the overall target size for searching sperm (48,49). Furthermore, the eggs of some species release sperm chemoattractants that increase the virtual size of eggs, increasing their chances of being contacted by sperm (50,51). Such egg accessory devices are thought to be energetically inexpensive relative to the actual ovicell itself (52), and so some have argued that selection due to the sperm environment will act more strongly on accessory structures than ovicell size per se (49).…”
mentioning
confidence: 99%